2014
DOI: 10.1063/1.4862541
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of nitrogen dissociation based on state-resolved cross sections

Abstract: State-resolved analyses of N + N2 are performed using the direct simulation Monte Carlo (DSMC) method. In describing the elastic collisions by a state-resolved method, a state-specific total cross section is proposed. The state-resolved method is constructed from the state-specific total cross section and the rovibrational state-to-state transition cross sections for bound-bound and bound-free transitions taken from a NASA database. This approach makes it possible to analyze the rotational-to-translational, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 22 publications
5
22
0
Order By: Relevance
“…In comparisons of the transition probabilities between the sections and VHS model, the difference is only produced by the difference o and 6 affects the total cross section in heavy-particle collisions and the total cross section is mostly dependent on the vibrational states of the molecule. In the previous thermochemical nonequilibrium studies of N 2 , the same result was also observed in that the state-specific total cross sections of N 2 are mostly depend on the vibrational states [19].…”
Section: (4)supporting
confidence: 65%
See 4 more Smart Citations
“…In comparisons of the transition probabilities between the sections and VHS model, the difference is only produced by the difference o and 6 affects the total cross section in heavy-particle collisions and the total cross section is mostly dependent on the vibrational states of the molecule. In the previous thermochemical nonequilibrium studies of N 2 , the same result was also observed in that the state-specific total cross sections of N 2 are mostly depend on the vibrational states [19].…”
Section: (4)supporting
confidence: 65%
“…(7) and (8), 6 dependent on the vibrational states of the molecule. In the previous thermo studies of N 2 , the same result was also observed in that the state-specific tota mostly depend on the vibrational states [19].…”
Section: (4)supporting
confidence: 64%
See 3 more Smart Citations